Analisis Jaringan Perpipaan Air Bersih Di PDAM Tirta Terubuk Kec. Bengkalis Kab. Bengkalis (Studi Kasus: Desa Kelapa Pati dan Kelurahan Damon) - Ramadhona, Witri; Putra, Sony Adiya; Halimatusadiyah (Sekolah Tinggi Teknologi Dumai, 2024)
Water is one of the needs of living things that must be met when needed. PDAM must provide maximum service to the community and be able to meet the community's demand for clean water which always increases every time, especially during peak water usage hours. This research is a case study by analyzing data. In data processing using the geometric method, exponential method and arithmetic method. The data used are population data from 2018 to 2022, data on the number of customers and water production data at PDAM Tirta Terubuk Kab. Bengkalis. The research stages include population growth projection, deviation suitability test and correlation coefficient, water demand analysis and simulation using the WaterCAD v8i program for 2037. The results showed that the calculation of clean water demand in 2037 obtained a total clean water demand in Village Kelapa Pati and Urban Village Damon of 40,914 l/s with a water loss of 20%. With a total distributed production capacity of 128 l/s, the amount of available source discharge is able to meet clean water needs until 2037. The available reservoir cannot meet the water demand. The pressure simulation results in the planning of the clean water distribution network have met the criteria, namely between 0.5 atm and 8 atm.